Unconventional post‐deposition chemical treatment on ultra‐thin H2TPP film grown on graphite. Issue 8 (7th May 2014) - Bussetti, G.; Campione, M.; Raimondo, L.; Yivlialin, R.; Finazzi, M.; Ciccacci, F.; Sassella, A.; Duò, L.
<x xml:space="preserve">Abstract</x> Free‐base H2TPP porphyrin layers have been grown on highly oriented pirolitic graphite by organic molecular beam epitaxy. The growth follows a Stranski‐Krastanov mode. By using a promising post growth chemical strategy we are able to reduce the number of 3D structures on the surface without perturbing the organic wetting layer. The strategy described in the work is fully generalizable and could be extended to other free‐base porphyrinic compounds. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>